Effect of variety, location, and irrigation on selected criteria for evaluating wheat as a feed for ruminants - Goldy, G.; Lenssen, Andrew William; Walters, T.; Riley, Jack G.; Posler, Gerry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
There were no significant differences in in vitro digestibility between wheat varieties, but there was a trend for differences due to locations. Location differences were much wider for test weight, 1000 kernel weight, hardness score and crude protein level than variety differences. Wheat from irrigated plots had higher grain yields and crude protein content, but lower test weights, 1000 kernel weight, and hardness values than wheat from fallow plots at the same location. There were no differences in digestibilites between fallow and irrigated wheat.
Keywords: Beef; Wheat; Ruminants; Yield; Protein